Function of the nuclear receptor FTZ‐F1 during the pupal stage in Drosophila melanogaster. (11th March 2014) - Sultan, Abdel‐Rahman S.; Oish, Yasuhiro; Ueda, Hitoshi
<x xml:space="preserve">Abstract</x> The nuclear receptor βFTZ‐F1 is expressed in most cells in a temporally specific manner, and its expression is induced immediately after decline in ecdysteroid levels. This factor plays important roles during embryogenesis, larval ecdysis, and early metamorphic stages. However, little is known about the expression pattern, regulation and function of this receptor during the pupal stage. We analyzed the expression pattern and regulation of ftz‐f1 during the pupal period, as well as the phenotypes of RNAi knockdown or mutant animals, to elucidate its function during this stage. Western blotting revealed that βFTZ‐F1 is expressed at a high level during the late pupal stage, and this expression is dependent on decreasing ecdysteroid levels. By immunohistological analysis of the late pupal stage, FTZ‐F1 was detected in the nuclei of most cells, but cytoplasmic localization was observed only in the oogonia and follicle cells of the ovary. Both the ftz‐f1 genetic mutant and temporally specific ftz‐f1 knockdown using RNAi during the pupal stage showed defects in eclosion and in the eye, the antennal segment, the wing and the leg, including bristle color and sclerosis. These results suggest that βFTZ‐F1 is expressed in most cells at the late pupal stage, under the control of ecdysteroids and plays important roles during pupal development.